Pengaruh Pemeriksaan Pajak, Pengenaan Sanksi Pajak Dan Pemahaman Wajib Pajak Terhadap Kepatuhan Wajib Pajak Pelaku UKM Yang Terdaftar Di KPP Pratama Karanganyar - Oktaviani, Ristiana; , Drs. M. Abdul Aris, M.Si (2014)
The purpose of this study is to know whether tax audit, tax sanction and tax knowledge have a significant impact on SME's tax payer's compliance either partially or simultaneously. Data were obtained from questionnaires completed by respondents listed in Taxation Office KPP Pratama Karanganyar in Central Java. A total of 95 questionnaires were returned in complete condition and can be processed. Using multiple regression techniques, the result shows that the tax audit significantly influence SME's tax payer compliance. Tax sanction and tax knowledge does not significantly affect the tax compliance of SME.